EVALUASI PELAKSANAAN PROGRAM KEPEMIMPINAN SMA AL-MUSLIM BEKASI JAWA BARAT Evaluasi Penelitian Menggunakan CIPP Daniel L. Stufflebeam - Siti Mugi Rahayu; Abdul Rahman Ghani (Universitas Muhammadiyah Tangerang, 2022)
ABSTRACTThis research aimed to evaluate leadership program at Senior High School Al Muslim in Bekasi. The evaluation model used was CIPP (Context, Input, Process, Product). The study found that the leadership program has been suitable to the policy of school foundation. However, regarding 2013 curriculum, the school needs to make leadership a separate subject. Based on teacher qualification, there is no special requirement to be a leadership teacher. The leadership teacher is appointed by the school foundation and considered to have competence in teaching leadership. In implementation, students need to be given chances to practice leadership skills; therefore, the teacher should use various but appropriate teaching methods. Leadership teachers should develop various scoring techniques to better find students’ skill. The study also found that leadership is important for students, alumni, and parents. Alumni stated that they got benefits from the leadership program.